Prostate Specific Antigen Testing Behaviors for Prostate Cancer Screening Among U.S. Immigrants: A Cross-sectional Analysis Using the National Health Interview Survey. Issue 1 (11th January 2023) - Hansen, Nathaniel F.; Linscott, Joshua A.; Hayn, Matthew H.; Ryan, Stephen T.; Sammon, Jesse D.
Abstract : Purpose: Immigrants constitute 14% of the U.S. population, and this group is especially vulnerable to poor health care access. Prior research demonstrates U.S. immigrants have low rates of guideline-concordant breast and colorectal screening, but prostate cancer screening has not previously been evaluated. We sought to characterize screening behaviors among U.S. immigrants and to consider possible mechanisms to enhance PSA-based screening for this population. Materials and Methods: Data were obtained from the 2010, 2013, 2015, and 2018 National Health Interview Survey reports, which were the recent survey years that included questions about PSA testing. Complex samples logistic regression was performed to assess the relationship between immigrant-specific characteristics including region of birth, citizenship status, length of residence within the U.S., English language proficiency, and history of PSA testing. Results: There were 22, 997 survey respondents; 3, 257 were foreign-born and 19, 740 were U.S.-born. Rates of PSA testing were much lower among the foreign-born population compared to the U.S.-born population (43% vs 60%). Citizenship status, length of residence in the U.S. for more than 15 years, and English proficiency were directly linked to increased rates of PSA testing. There was significant variability in PSA testing among immigrant subgroups and Asian immigrants had the lowest rate of PSA testing. Annual physician visits and English language proficiency were associated with increased PSA testing among the U.S. immigrant population. Conclusions: Immigrants have relatively low rates of PSA testing. Improving health care utilization and language services may help to narrow the gap in guideline-concordant prostate cancer screening between immigrants and nonimmigrants.